2014
DOI: 10.1097/hnp.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Dimensions of Care

Abstract: The nurses' role in providing spiritual care to in-hospital patients is not clearly outlined in the Republic of Ireland (ROI). This and other deficits reveal that there are current gaps in nurses' knowledge and confidence in this area. In response, an educational innovation has been developed and this article reports on its development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Some scholars [47] have incorporated religious and communication skills into teaching. Timmins et al [48] concluded that spiritual content education includes personal understanding of spirituality and spiritual concepts and identification of patients’ spiritual needs. Ross et al [23] showed that nurses’ personal beliefs and values and their spirituality and sensitivity levels can affect spiritual care outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Some scholars [47] have incorporated religious and communication skills into teaching. Timmins et al [48] concluded that spiritual content education includes personal understanding of spirituality and spiritual concepts and identification of patients’ spiritual needs. Ross et al [23] showed that nurses’ personal beliefs and values and their spirituality and sensitivity levels can affect spiritual care outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Dewing ( 2008 ) highlighted that every person has an absolute value and that every person should be embedded within a social group that provides integrity, continuity and stability. Friendly and cheerful caring, respecting privacy and dignity, should be provided by nursing staff (Timmins et al., 2014 ) in all nursing homes. Thus, nursing care for people living with dementia must be compassionate and respectful.…”
Section: Discussionmentioning
confidence: 99%
“…This is resultant from various factors including confusion between religion and spirituality and lack of role clarity. There is also an identified lack of educational preparedness of healthcare staff, and thus a lack of confidence and competence to deliver spiritual care (Timmins et al 2014). There is also a risk or concern about proselytizing.…”
Section: Recommendationsmentioning
confidence: 99%